Perempuan Pencari Nafkah dalam Perspektif Imam Shafi’i dan Feminisme Liberal - Zanida Iqraminati; Isnatin Ulfah; Rifqi Annurrahmadhani; Mipa Andakhir (Jurnal Antologi Hukum, 2022)
: Marriage raises the rights and obligations of husband and wife, but there is a perception of the obligation for the wife to work to provide for the family. The uniqueness is that a wife who doesn't work for a living will get stereotyped by society. The point of the problem is what is the perspective of Imam Shafi'i and liberal feminism regarding the rights and obligations of women as breadwinner wives in the Panjen Complex, Petung Hamlet, Tempuran Village, Sawoo District, Ponorogo Regency. This research is a field research with a qualitative approach. The results of the study concluded: first, according to Imam Shafi'i, the rights of a wife are appropriate, including material maintenance, dowry, and part of spiritual maintenance. The wife's obligations according to Imam Shafi'i, the wife informants had carried out their obligations as wives, namely obeying their husbands and providing services to their husbands. Still, there were discrepancies related to domestic obligations. Second, rights according to liberal feminism, the wife, as a rational being who prioritizes rights over goodness, does not get her right to choose her role (housewife) because she obeys the prestige (compulsion) of the stereotypes that come to her. Pernikahan menimbulkan hak dan kewajiban suami istri, namun terdapat persepsi kewajiban bagi istri untuk wajib bekerja mencari nafkah keluarga. Keunikannya adalah di mana istri yang tidak ikut mencari nafkah dia akan mendapatkan stereotip oleh masyarakat. Titik permasalahannya yakni bagaimana perspektif Imam Shāfi’ī dan feminisme liberal tentang hak dan kewajiban perempuan sebagai istri pencari nafkah di Komplek Panjen Dusun Petung Desa Tempuran Kecamatan Sawoo Kabupaten Ponorogo. Penelitian ini merupakan penelitian lapangan (field research) dengan pendekatan kualitatif. Hasil penelitian menyimpulkan: pertama, hak istri menurut Imam Shāfi’ī sudah sesuai, meliputi nafkah kebendaan, mahar, dan sebagian nafkah batin. Kewajiban istri menurut Imam Shāfi’i, para informan istri telah melaksanakan kewajibannya sebagai istri yakni taat pada suami, dan memberi pelayanan kepada suami, namun terdapat ketidaksesuaian yakni terkait kewajiban domestik. Kedua, hak menurut feminisme liberal, istri sebagai makhluk yang rasional yang memprioritaskan hak dari pada kebaikan tidak mendapatkan haknya untuk memilih perannya (ibu rumah tangga) disebabkan menuruti gengsi (keterpaksaan) akan stereotip yang datang padanya.